Averting a Water War through Surface Water Management in Pakistan: Averting a Water War through Surface Water Management in Pakistan - Shahzad, Naeem (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
Water is life line. Pakistan is close to becoming a water scarce country owing to our own poor water management coupled with exploitation of water resources by our neighbouring country India. If unfortunately, we become dependent on our neighbours for meeting our water requirements, they need not to wage war to enforce their dictations on us. A quantitative analysis has been carried out from extensive literature review and research studies. The paper highlights the growing water scarcity issues of Pakistan and control of water resources by India, contrary to the Indus Water Treaty. It also suggests the water management and conservation practices and sheds light on exploring new possibilities to meet our growing water demands. This study emphasizes in detail about the repercussions if we fail to realize the importance of this precious commodity and underlines importance of the needed institutional reforms. It also suggests the way forward in order to be able to meet the future challenges to avert the imminent water crisis in our country.